Kedatangan dan Penyebaran Islam di Asia Tenggara: Telaah Teoritik tentang Proses Islamisasi Nusantara - Amin, Faizal; Ananda, Rifki Abror (Universitas Islam Negeri Raden Intan Lampung, 2018)
This article studies some theories about the introduction and spread of Islam in South East Asia in the context of Islamisation of Nusantara. The relevance is do tue history of the introduction of Islam in South East Asia is one of the most important points to understand South East Asian Islam. Nevertheless, it has been the most probelmatic and unclear. The academic debate have been accured among the scholars from West and South East Asian. They have pointed out some evidents, interpretations, and argumentations to construct the theory of introduction and spread of Islam in South East Asia. This article examines five of those theories to answer three core problem, namely the origin place of Islam, the actors who came with, and the time of it’s introduction. The five of those theories are Indian, Arabian, Persian, Chinesee, and Acomodative Theories. The debates and polemic of those theories will never be`the end becouse of the lack of data and the patisan interest to some core problems while ignore the other ones. This article not only talk about some factors and channels of Islamisation, but also describes some characteristics of Shoth East Asian Islam.